KAJIAN PRODUKSI UDANG VANNAMEI (Litopenaeus vannamei) PADA TAMBAK PLASTIK DENGAN PADAT TEBAR BERBEDA - Agung Doni Anggoro; Muhamad Agus; Tri Yusufi Mardiana (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
This research aims to determine the effect of different stock density in plastic ponds for the production of vannamei shrimp (Litopenaeus vannamei). The method used in this research is explorative by focusing on case studies. Different stock density in this research were 60,72,80 shrimps/m2. Result showed that stock density 84 shrimps/m2 gives the best production. The highest survival rate (SR) was obtained in stocking solids of 60 shrimp /m2 around 94%. The smallest feed conversion value occurs in stocking stock 60 shrimps/m2 of 1.28. Water quality parameters for research is still in the range of optimum temperature about 27.8 to 31.3 °C, dissolved oxygen (DO) 6.7 to 8.1 ppm, pH 7.8 to 8.5, salinity 31,9- 33.9 ppt and brightness from 30.3 to 35.3 cm.